Upregulation of Linc00284 Promotes Lung Cancer Progression by Regulating the miR-205-3p/c-Met Axis - Sheng, Wang; Guo, Weixi; Lu, Fang; Liu, Hongming; Xia, Rongmu; Dong, Feng (Frontiers in Genetics, 2021)
Lung cancer (LC) is a malignant tumor with the highest incidence and mortality rates worldwide. Linc00284, a long non-coding RNA, is a newly discovered regulator of LC. This study aimed to explore the role of Linc00284 in LC progression. Gene expression levels were detected by RT-qPCR and/or western blot analysis. Cell migratory and invasive capabilities were measured by wound healing and transwell assays. Subcutaneous xenograft models were constructed to examine tumor growth of LC cells. Data showed that Linc00284 was significantly upregulated in LC tissues compared to adjacent normal lung tissues and predicted poor prognosis in patients with LC. In vitro, Linc00284 was highly expressed in LC cells and was mainly localized in the cytoplasm. Mechanistically, Linc00284 directly bound to miR-205-3p, leading to the upregulation of c-Met expression. A significant negative correlation was observed between Linc00284 and miR-205-3p expression levels, and the Linc00284 level was positively correlated with the c-Met expression. Linc00284/miR-205-3p/c-Met regulatory axis promotes LC cell proliferation, migration, and invasion. Furthermore, the in vivo results indicated that Linc00284 knockdown markedly suppressed tumor growth. Taken together, these data suggest that Linc00284 facilitates LC progression by targeting the miR-205-3p/c-Met axis, which may be a potential target for LC treatment.